Latino Stars in Major League Baseball: From Bobby Abreu to Carlos Zambrano - Weeks, Jonathan (Rowman & Littlefield Publishers, 2017)
Some of the best players in Major League Baseball were born outside the United States, with Latino players representing one of the fastest growing ethnicities in the league. Current and former stars such as Albert Pujols, Rod Carew, and Miguel Cabrera all found incredible success in MLB. They have won major awards, guided their teams to the postseason, played in All-Star games, and an elite few have been enshrined in the Baseball Hall of Fame. Latino Stars in Major League Baseball: From Bobby Abreu to Carlos Zambrano celebrates the ever-increasing diversity of baseball in America. It includes more than 140 in-depth profiles of retired and active ballplayers representing countries across Latin America and the Caribbean. For many of these players, the road to “The Show” wasn’t easy—discrimination, poverty, language barriers, and government restrictions are major obstacles that Latino players have faced in the past and continue to face today. Author Jonathan Weeks covers these struggles and more in the profiles, showing the players’ strength, resiliency, and ultimately, their rise to the top of professional baseball. Latino Stars in Major League Baseball is a definitive collection of the best and brightest Latino stars both past and present. Full of colorful anecdotes and inspiring stories, this book provides a rich understanding of Latino players’ impact on baseball in the United States.